The link between income inequality and health in Europe, adding strength dimensions of primary care to the equation. (March 2018) - Detollenaere, Jens; Desmarest, Ann-Sophie; Boeckxstaens, Pauline; Willems, Sara
Abstract: Income inequality has been clearly associated with reduced population health. A body of evidence suggests that a strong primary care system may mitigate this negative association. The aim of this study is to assess the strength of the primary care system's effect on the inverse association between income inequality and health in Europe. Health is operationalised using four cross-sectional outcomes: self-rated health, life expectancy, mental well-being, and infant mortality. Strength of the primary care system is measured using the framework of the Primary Health Care Activity Monitor Europe, and income inequality by the Gini coefficient. Multiple regression models with interaction terms were used. The results confirm that especially the structure and continuity dimension of primary care strength can buffer the inverse association between income inequality and health. European policymakers should therefore focus on strengthening primary care systems in order to reduce inequity in health. Highlights: This study confirms the inverse association between income inequality and health. The structure dimension of primary care strength buffers this inverse association. The continuity dimension of primary care strength buffers this inverse association. The analyses reveal an aggravating or mixed effect of other primary care dimensions.